Fructose Laurate Enzymatic Synthesis by Resin D301 Immobilized Candida sp. 99-125 Lipase - Zhu, Kai; Lu, Jiaang; Hu, Jun; Wang, Hailing; Xu, Ning; Han, Pingfang; Wei, Ping (Asian Journal of Chemistry, 2011)
Sugar ester synthesis is catalyzed by the immobilized lipase of resin D301, which is obtained from immobilizing free Candida sp. lipase on the weakly basic anion exchange resin D301. This reaction requires butanone as a solvent, as well as fructose and lauric acid substrates. In this study, we designed and optimized an orthogonal immobilized enzyme catalyzed synthesis. The optimized reaction is incubated at 50 ºC for 24 h with 20 mL of methyl ethyl ketone as a solvent and a rotation speed of 180 rpm. The optimal molecular sieve concentration was 75 g/L, the substrate ratio was 1.5:1 and the enzyme concentration was 10 g/L. Under these optimal conditions, the maximum relative per cent conversion of lauric acid was 60 % with the difructose laurate substrate. The products were analyzed by TLC and 13C NMR and the resulting products were 1-β-mono-D-fructopyranose laurate, which had an Rf of 0.44 and 1,6-β-di-Dfructopyranose laurate, which had an Rf of 0.79. Compared to traditional reactions in solvents, the solvent-free system was easier to separate and purify, which made the procedure both more cost and time effective.